Diagnostic Value of PET/CT for Ovarian Cancer Recurrence or Metastasis in Postoperative Patients With Elevated Serum CA125 Levels: A Systematic Review and Meta‐Analysis - Zuowei Zou; Luhua Xia; Saikang Tang; Lin Lin; Quanyang Wu; Donghui Hou; Shijun Zhao (Cancer Innovation)
ABSTRACT Background Ovarian cancer patients with elevated serum CA125 levels after operation have a high incidence of relapse or metastasis. 18F‐FDG PET/CT is an effective imaging method for identifying recurrent or metastatic lesions. This study systematically investigated the diagnostic value of 18F‐FDG PET/CT in this patient population. Methods A systematic search of PubMed, Embase, Cochrane Library (Central), Web of Science (SCI‐Expanded), and Chinese databases (CNKI, VIP database, Wan Fang Data, CBM) was performed. Studies that evaluated the diagnostic value of 18F‐FDG PET/CT for relapse or dissemination in postoperative ovarian cancer patients with elevated serum CA125 levels were included. The methodological quality of the studies was evaluated using the Quality Assessment of Diagnostic Accuracy Studies 2 tool. Data were analyzed for heterogeneity using Meta‐Disc 1.4 software. Sensitivity analysis and release bias evaluation were conducted using STATA 14.0 software. Thirteen studies (including 421 female patients) qualified for the meta‐analysis. The pooled sensitivity and specificity of 18F‐FDG PET/CT were 0.94 (95% CI: 0.91–0.97) and 0.83 (95% CI: 0.71–0.91), respectively. The pooled positive likelihood proportion was 4.59 (95% CI: 2.81–7.51), the pooled negative likelihood proportion was 0.09 (95% CI: 0.05–0.15), and the pooled diagnostic odds ratio was 64.22 (95% CI: 27.21–151.57). The area under the curve was 0.9379. A sensitivity analysis and publication bias test indicated that the outcomes were steady, and there was no reporting bias. Conclusions 18F‐FDG PET/CT has high diagnostic veracity for identifying recurrence or metastasis in ovarian cancer cases with increased serum CA125 levels after surgery. It can accurately detect recurrent or metastatic lesions, providing valuable information for clinical decision‐making.